Effect of Calcium Carbonate Level with or without Benzoic Acid on Weanling Pig Growth Performance, Fecal Dry Matter, and Blood Calcium and Phosphorus Concentrations - Alan J. Warner; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 360 barrows (DNA Line 200 × 400; initially 13.6 ± 0.07 lb) were used in a 38-d study to evaluate the interactive effects of added dietary calcium carbonate and benzoic acid on nursery pig growth performance, fecal dry matter, and blood Ca and P concentration. Upon arrival to the nursery research facility, pigs were randomly assigned to pens (5 pigs per pen) and pens were allotted to 1 of 6 dietary treatments with 12 pens per treatment. Dietary treatments were formulated to provide 0.45, 0.90, or 1.35% calcium carbonate, with or without 0.5% benzoic acid (VevoVitall, DSM Nutritional Products, Parsippany, NJ). Diets were fed in three phases with phase 1 treatment diets (0.66, 0.83, or 1.00% Ca) fed from weaning (d 0) to d 10; phase 2 treatment diets (0.54, 0.72, or 0.89% Ca) fed from d 10 to 24; and a common phase 3 diet from d 24 to 38 (0.68% Ca). Standardized total tract P concentrations were formulated to 0.58, 0.51, and 0.47 in phases 1, 2, and 3, respectively. There were no calcium carbonate × benzoic acid interactions observed for any response criteria (P>0.10). From d 0 to 10 (phase 1), there was evidence for benzoic acid to marginally increase (P= 0.092) ADG and significantly increase (P= 0.042) ADFI. From d 10 to 24 (phase 2), F/G improved (P= 0.022) as the level of calcium carbonate decreased. For the overall experimental period (d 0 to 24), there was a tendency for benzoic acid to improve (P= 0.056) ADG and (P= 0.071) ADFI, as well as an improvement (linear,P= 0.014) in F/G as calcium carbonate in the diet decreased. During the common period (d 24 to 38), pigs previously fed benzoic acid had increased (P= 0.045) ADG and marginally increased (P= 0.091) ADFI. For the overall study, pigs fed benzoic acid had increased (P= 0.011) ADG and (P= 0.030) ADFI and marginally improved (P= 0.096) F/G. For fecal DM, there was no observed evidence (P>0.10) for differences among treatments. For serum analysis, serum Ca decreased (P<0.001) as the level of dietary calcium carbonate decreased. These data suggests that lower levels of calcium carbonate may improve feed efficiency in the early nursery period. Also, nursery pigs fed benzoic acid had increased ADG and ADFI, and tended to have improved F/G.
Keywords: benzoic acid; calcium; calcium carbonate; nursery pig; phosphorus